PARTUTURON DEGRADATION ON CONSTRUCTION CHARACTER OF STUDENT PARTICIPANTS - Nur - Afifah; Husniah Ramadhani Pulungan; Eli Marlina Harahap (FORUM PAEDAGOGIK, 2022)
This study aims to examine the degraded understanding of partitions among the younger generation as a form of politeness in building student character. The research method is qualitative and descriptive with data collection techniques in the form of listening and recording 20 class XII students of Madrasah Aliyah Al-Ahliyah Aek Badak. In addition, to confirm the data, interviews were also conducted as data validation with three informants. The results showed that based on test results, out of 67 speeches, not all students were able to answer half of the 67 speeches. This confirms and proves that there has been a degradation in students' understanding of class names which will automatically affect the way they behave in society in everyday life. The values of character education that are expected to be instilled starting from mutual cooperation, togetherness, rights and obligations, tolerance, compassion, and holong, so that kinship is maintained properly have not all been implemented because of the understanding of the naming of the partutoron of the students being tested. It's not finished yet, so it takes a shared responsibility to fix it.